Pediatric Perioperative Pulmonary Arterial Hypertension: A Case-Based Primer - Shilpa Shah; Jacqueline R. Szmuszkovicz (MDPI AG, 2017)
The perioperative period is an extremely tenuous time for the pediatric patient with pulmonary arterial hypertension. This article will discuss a multidisciplinary approach to preoperative planning, the importance of early identification of pulmonary hypertensive crises, and practical strategies for postoperative management for this unique group of children.